Delays in Initial Treatment Contact after First Onset of a Mental Disorder - Wang, Philip S (Blackwell Science Inc, 2004)
OBJECTIVE: To examine nationally representative patterns and predictors of delays in contacting a professional after first onset of a mental disorder. DATA SOURCES: The National Comorbidity Survey, a nationally representative survey of 8,098 respondents aged 15–54. STUDY DESIGN: Cross-sectional survey. DATA COLLECTION: Assessed lifetime DSM-III-R mental disorders using a modified version of the Composite International Diagnostic Interview (CIDI). Obtained reports on age at onset of disorders and age of first treatment contact with each of six types of professionals (general medical doctors, psychiatrists, other mental health specialists, religious professionals, human services professionals, and alternative treatment professionals). Used Kaplan–Meier (KM) curves to estimate cumulative lifetime probabilities of treatment contact after first onset of a mental disorder. Used survival analysis to study the predictors of delays in making treatment contact. PRINCIPAL FINDINGS: The vast majority (80.1 percent) of people with a lifetime DSM-III-R disorder eventually make treatment contact, although delays average more than a decade. The duration of delay is related to less serious disorders, younger age at onset, and older age at interview. There is no evidence that delay in initial contact with a health care professional is increased by earlier contact with other non–health-care professionals. CONCLUSIONS: Within the limits of recalling lifetime events, it appears that delays in initial treatment contact are an important component of the larger problem of unmet need for mental health care. Interventions are needed to decrease these delays.